2019
DOI: 10.1111/nph.15829
|View full text |Cite
|
Sign up to set email alerts
|

Neofunctionalisation of basic helix−loop−helix proteins occurred when embryophytes colonised the land

Abstract: ROOT HAIR DEFECTIVE SIX‐LIKE (RSL) genes control the development of structures from single cells at the surface of embryophytes (land plants) such as rhizoids and root hairs. RSL proteins constitute a subclass (VIIIc) of the basic helix–loop–helix (bHLH) class VIII transcription factor family. The Charophyceae form the only class of streptophyte algae with tissue‐like structures and rhizoids. To determine if the function of RSL genes in the control of cell differentiation in embryophytes was inherited from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 79 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…The mechanisms promoting rhizoid development are conserved between bryophyte groups, and also conserved with mechanisms regulating root hair development in flowering plant sporophytes [116][117][118] . The bHLH transcription factors involved predate the origin of land plants 119 , but a Chara braunii bHLHVIII sister gene to the land plant RSL gene clade functions non-equivalently to land plant genes, suggesting that neofunctionalisation was involved in the emergence of rhizoid-based rooting systems 120 .…”
Section: Vegetative Shootsmentioning
confidence: 99%
“…The mechanisms promoting rhizoid development are conserved between bryophyte groups, and also conserved with mechanisms regulating root hair development in flowering plant sporophytes [116][117][118] . The bHLH transcription factors involved predate the origin of land plants 119 , but a Chara braunii bHLHVIII sister gene to the land plant RSL gene clade functions non-equivalently to land plant genes, suggesting that neofunctionalisation was involved in the emergence of rhizoid-based rooting systems 120 .…”
Section: Vegetative Shootsmentioning
confidence: 99%
“…RSL genes are found extensively in all land plant genomes and also within the charophyte algae (N. D. Pires et al, 2013). Phylogenetic studies have revealed that two classes of RSL genes (Classes I and II) exist in land plants, and that these likely arose in the charophyte lineage, or in the earliest colonizers of land (Bonnot et al, 2019; N. D. Pires et al, 2013). RSL genes regulate the development of epidermal structures, most notably root hairs and rhizoids, but also asexual propagules or secretory hairs in extant land plants (Jang & Dolan, 2011; Jang et al, 2011; Kim & Dolan, 2016; Masucci & Schiefelbein, 1994; B. Menand, Yi, et al, 2007; Proust et al, 2016; K. Yi et al, 2010).…”
Section: Root Hair Defective Six‐like (Rsl)mentioning
confidence: 99%
“…RSL genes are found extensively in all land plant genomes and also within the charophyte algae (N. D. Pires et al, 2013). Phylogenetic studies have revealed that two classes of RSL genes (Classes I and II) exist in land plants, and that these likely arose in the charophyte lineage, or in the earliest colonizers of land (Bonnot et al, 2019;N. D. Pires et al, 2013).…”
Section: Root Hair Defective Six-like (Rsl)mentioning
confidence: 99%
“…S1), exemplifying once more that the structurally simple, yet diverse 'saccoderm desmids' (traditionally Mesotaeniaceae) are still heavily understudied (Gontcharov et al, 2004;Gontcharov & Melkonian, 2010). However, these phylogenetically diverse life forms show clear cell morphological differences (Gontcharov, 2008) and, recently, gained importance for evolutionary inferences (Bonnot et al, 2019;Cheng et al, 2019;Liang et al, 2019;Xu et al, 2019;Philippe et al, 2020), so that a taxonomic revision of these algae is desirable.…”
Section: Serritaenia Comprises Genetically Diverse Microalgae With Subtle Morphological Differencesmentioning
confidence: 99%